IMPACTS OF BLACK FEMINISM ON THE PROMOTION AND PROTECTION OF BLACK WOMEN’S RIGHTS - Franchini, Rafaelle; Cazelatto, Caio Eduardo Costa; Cardin, Valéria Silva Galdino (Revista Direito e Sexualidade, 2021)
This article analyzed, through bibliographic review, the social movement of feminism as an instrument of protection and promotion of black women’s rights. To this end, the historical development of the feminist movement was investigated, with a focus on European countries and the United States of America, as well as the legal developments and achievements obtained by Brazilian black women from the Carta das Mulheres aos Constituintes or Letter of Women to the Constituents. It explored the fundamental rights that were claimed and achieved by the feminist movement for black women. Thus, it was found that the trajectory of black women is strongly marked by the reflexes that slavery and social marginalization have historically brought to this vulnerable segment, as it was also observed that the social movement of black feminism ended up not effectively representing the claims of black women, who, for the most part, are still related to the consequences of the period of slavery, such as low or no education, underemployment, victims of violence against women, among others.